2021
DOI: 10.1029/2020ja028802
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Fabry–Perot Interferometer and Meteor Radar Wind Measurements Near the Polar Mesopause Region

Abstract: The FPI can provide reliable height-averaged winds even under a strong wind shear near the mesopause region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The first is that the intercepts are close to zero. The second is that ERWIN consistently measures winds that are on average factors of 0.6 to 0.7 of those of the MWR, a result that has also been noted in recent Fabry-Perot, MWR comparisons [Yu et al (2017); Lee et al (2021)].…”
Section: Discussionmentioning
confidence: 55%
“…The first is that the intercepts are close to zero. The second is that ERWIN consistently measures winds that are on average factors of 0.6 to 0.7 of those of the MWR, a result that has also been noted in recent Fabry-Perot, MWR comparisons [Yu et al (2017); Lee et al (2021)].…”
Section: Discussionmentioning
confidence: 55%
“…Lee et al [30] compared the winds at the two altitudes of 87 and 97 km retrieved by using the OH and OI emissions observed by the FPI and MR at King Sejong Station in Antarctica (62.22 • S, 58.79 • W), and they suggested that the two wind measurements agree well. In addition, Gu et al [31] conducted a comparison between the winds at 87 km observed by the Kunming FPI (OH emission) and the 53.1 MHz MR and similarly indicated a good correlation between the two techniques; moreover, they also reported that the FPI estimates were smaller than the MR measurements by about 30%, and the bias was larger than for MF radar winds.…”
Section: Discussionmentioning
confidence: 99%
“…Meteor radars on the ground have been equipped to measure neutral winds and temperature in the lower part of the MLT region (Beard et al., 1997; Beldon & Mitchell, 2010; Day & Mitchell, 2010; Huang et al., 2013; Kam et al., 2021; C. Lee et al., 2021). Meteoroids entering the Earth's atmosphere leave ionization trails, and meteor radars detect backscattering echoes of transmitted radio signals from meteor trails.…”
Section: Introductionmentioning
confidence: 99%
“…Meteor radars on the ground have been equipped to measure neutral winds and temperature in the lower part of the MLT region (Beard et al, 1997;Beldon & Mitchell, 2010;Day & Mitchell, 2010;Huang et al, 2013;Kam et al, 2021;C. Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%